Deep application of controlled-release urea increases the yield and saponin content of Panax notoginseng by regulating soil nitrate distribution - Su, Yun-xia; Zhao, Ping; Jia, Li-jie; Cao, Yuan-feng; Liu, Guan-ze; Chen, Jun-wen; Yang, Sheng-chao; Zhou, Yan-li; Long, Guang-qiang (Frontiers in Plant Science, 2025)
IntroductionThe deep application of controlled-release urea (CRU) offers potential advantages for crops with extended growth periods. However, its effects on P. notoginseng yield and quality, a medicinal plant with a prolonged nutrient acquisition duration, remain unclear.MethodsIn this study, we conducted a two-year field plot experiment to investigate the effect of CRU on P. notoginseng with three placement depths (0, 6, and 12 cm denoted as R0, R6, and R12, respectively) at an application dosage of 250 kg N ha-1 with biochar addition (R6B) and 20% N reduction (R6R) based on the R6, with conventional fertilization (250 kg N ha-1, common urea) serving as the control (CK).ResultsOur results indicated that yields increased by 27.1–37.6% with R0, R6, R12, and R6B, while remaining stable with R6R compared to CK. Simultaneously, the total saponin content in the roots of R6, R6B, and R6R was improved by 14.3–38.1%, compared to CK. The distribution depth of soil NO3⁻-N and plant roots increased with the depth of CRU application, with a high overlap in time and space, indicating P. notoginseng N uptake peaked when CRU was applied at a depth of 6 cm (R6). Structural equation modeling indicated that soil NO3⁻-N supply in specific microareas directly affected the N uptake and increased total saponin content by increasing root length and surface area, thus boosting yield.ConclusionThis study identifies that the deep application of CRU at a depth of 6 cm has the potential to enhance both yield and quality of P. notoginseng and highlights that the spatial-temporal matching of soil NO₃⁻-N and plant roots was the key to applying CRU to ensure high yield and quality.